GRAPHICAL MODELS OF STANDARD DATA STRUCTURES AND THEIR IMPORTANCE IN TEACHING PROGRAMMING - STOFFOVA, Veronika; UDVAROS, Jozsef (Trends in education, 2013)
The article gives a graphic description of the models of standard data structures, which allow the beginner programmer to create the right idea about their implementation in computer memory. True understanding of the structure of a particular type of data clusters into larger units, their hierarchical construction permit to understand the rules of access to their individual elements, and the possibility of addressing individual elements as well as more complex data files allows their proper use in programs to solve various tasks. The models are based on the linear structure of memory (memory is viewed as an ordered set of addressable units - bytes).
Keywords: graphical models; data structures; file